Sagot :
Answer:
p(x)=6x^2-5x+16x
2
−5x+1
FORMULA:
QUADRATIC EQUATION P(X)=X^2-(SUM OF ZEROES)X +PRODUCT OF ZEROES.
EXPLANATION:
\alphaα =1/2
\betaβ =1/3
p(x)= x^2-x(\alpha+\beta)+\alpha\betax
2
−x(α+β)+αβ
p(x)=x^2-x(1/2+1/3)+(1/2)(1/3)x
2
−x(1/2+1/3)+(1/2)(1/3)
p(x)=x^2-x(5/6)+(1/6)x
2
−x(5/6)+(1/6)
p(x)=x^2-(5/6)x+(1/6)x
2
−(5/6)x+(1/6)
p(x)=6x^2-5x+16x
2
−5x+1
Answer:
work backwards to find the factors from the roots, then multiply the factors together.
[tex]y=x^{2} -\frac{7x}{6} +\frac{1}{3}[/tex]
Step-by-step explanation: